Gambaran Pengetahuan Masyarakat terkait Pertolongan Pertama Korban Kecelakaan Lalu Lintas - Ratna Mahmud; Muhammad Sahlan Zamaa; Esse Puji Pawenrusi; Hasdar (Cindoku : Jurnal Keperawatan dan Ilmu Kesehatan, 2026)
A traffic accident is an unexpected and unintentional incident on the road that can result in injury or even death. Providing first aid appropriate to the victim's condition is crucial for ordinary people before medical personnel can provide further treatment. The Sungguminasa Police Traffic Unit database in Gowa Regency indicates that throughout 2024, there were 78 accidents with 4 fatalities. This study aims to determine the public's knowledge about first aid for traffic accident victims in Bontoramba Village, Somba Opu District, Gowa Regency. This study used a descriptive survey research method. The population was 657 people with a sample size of 80 respondents using a simple random sampling technique. The results of this study indicate that most of the community (56.25%) have insufficient knowledge regarding providing first aid to accident victims. The conclusion of this study is that public knowledge regarding first aid for traffic accidents is still largely lacking. It is recommended that local community health center health promotion officers provide information and education as well as simulations on first aid for traffic accident victims through ongoing health education activities. And to the Gowa district government to evaluate and improve the service system in the field of completeness of first aid facilities and infrastructure for traffic accident victims.